Uptake of branched-chain alpha-keto acids in Bacillus subtilis. - Goldstein, B J (1976)
Bacillus subtilis has a constitutive system for the uptake of alpha-keto-beta-methylvalerate, alpha-ketoisovalerate, and (probably) alpha-ketoisocaproate. A mutation, kauA1, which blocks the uptake of alpha-keto-beta-methylvalerate and alpha-ketoisovalerate, is located between metB and citK on the B. subtilis chromosome.